المؤثرات الموسيقية ودلالتها الجمالية في العرض المسرحي العراقي: تذكر أيها الجسد أنموذجا - طاهر، شيماء حسين (جامعة واسط - كلية الآداب, 2021)
The musical influence is an important element in the process of receiving because of its implications. It is an important element that reveals the general atmosphere and in a semantic, aesthetic and indicative center, that supports the presentation. The first chapter included (the theoretical framework) and included the research problem represented by the following question (Where do the aesthetics of the musical influence lie in the presentation and what is its significance? The aesthetic in the Iraqi theatrical performance), and the importance of the research included shedding light on the musical influence as an aesthetic sign that has various connotations in the theatrical performance system. The aim of the research is to identify the musical influence in the Iraqi theatrical performance and the mechanisms of its operation as an aesthetic sign that contributes to the taste of the show and its interpretation. The research was concluded with definitions, and the second chapter included two topics, the first section included musical influences as an aesthetic mediator, while the second topic included the musical influence as a psychological aesthetic mediator. The second chapter concluded with the indicators that resulted from the theoretical framework. The third chapter is devoted (research procedures) and the indicators that resulted from the theoretical framework as a tool for analysis within a descriptive (analytical) approach and scenes of performances and photographs to come to the analysis of the presentation (Remember, O Body) directed by (Mohamed Muayyad) in (2010). And in an intentional way for reasons justified by the researcher to keep pace with the investigations and to achieve the objectives of the research and solve a problem. The fourth chapter concluded a number of results, the most important of which are: 1-The musical influencer turns into a sign that transmits its code through kinetic performance. 2-The musical influence turns into a signal system that reduces language. Then conclude with a summary of the search words.
يعد المؤثر الموسيقي عنصر مهم في عملية التلقي لما يحمله من دلالات فهو عنصر مهم كاشف للجو العام وبشكل مركز دلالي وجمالي وإشاري يدعم العرض، تضمن الفصل الأول (الإطار النظري) والمتضمن مشكلة البحث المتمثلة بالتساؤل التالي (أين تكمن جماليات المؤثر الموسيقي في العرض وما هي دلالتها الجمالية في العرض المسرحي العراقي)، كما تضمن أهمية البحث تسليط الضوء على المؤثر الموسيقي كعلامة جمالية لها دلالات متنوعة في منظومة العرض المسرحي. أما هدف البحث هو التعرف على المؤثر الموسيقي في العرض المسرحي العراقي وآليات اشتغاله كعلامة جمالية تسهم في تذوق العرض وتأويله تذكر أيها الجسد انموذجا وشمل الفصل حدود البحث التي حددت مكانيا في العراق وزمانيا و2012م وموضوعيا المؤثرات الموسيقية ودلالتها الجمالية في العرض المسرحي العراقي) ومن ثم تحديد مصطلحات البحث واختم بالتعريفات وقد احتوى الفصل الثاني متضمن مبحثين المبحث الأول المؤثرات الموسيقية بوصفها وسيطا جماليا أما المبحث الثاني المؤثر الموسيقي بوصفه وسيط جمالي نفسي. واختتم الفصل الثاني بالمؤشرات التي أسفر عنها الإطار النظري. وكرس الفصل الثالث (إجراءات البحث) والمؤشرات التي أسفر عنها الإطار النظري بوصفها أداة للتحليل ضمن منهج وصفي (تحليلي) ومشاهد العروض والصور الفوتوغرافية ليأتي تحليل عرض (تذكر أيها الجسد) المخرج (محمد مؤيد (عام (2010). وبالطريقة القصدية لأسباب سوغتها الباحثة لمسايرة المباحث ولتحقيق أهداف البحث وحل مشكلة ولخلص الفصل الرابع إلى عدد من النتائج أهمها: 1-المؤثر الموسيقي يتحول إلى علامة تبث شفرتها من خلال الأداء الحركي. 2-يتحول المؤثر الموسيقي إلى نظام إشاري يعمل على اختزال اللغة. ثم اختتم بملخص البحث الكلمات.
Keywords: الحضارات القديمة -- المسرح العراقي -- الالات الموسيقية -- الأداء الحركي